2001
DOI: 10.1080/000155501750208146
|View full text |Cite
|
Sign up to set email alerts
|

No Human Leukocyte Antigen-A, -B or -DR Association in Swedish Patients with Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is a cicatrizing, inflammatory and recurrent disease restricted to inverse skin, such as that of the axilla and groin of younger adults. In a previous study, using serological tissue-typing techniques, no significant increases in the human leukocyte antigen (HLA)-A and -B specificities were found in patients with HS. The aim of this study was to determine the frequencies of HLA-A, -B and, for the first time, HLA-DR alleles, using genomic tissue-typing methods in patients with HS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…No association has been found with HLA-B or HLA-DR types,20 and an initial report suggesting involvement of chromosome 1p21.1–1q25.321 was not confirmed in two large, multigeneration pedigrees (96 individuals, 25 affected) 19. CARD15 polymorphisms were also excluded in a pilot study and a case series 22 23.…”
Section: Risk Factors: Smoking Obesity and Family Historymentioning
confidence: 91%
“…No association has been found with HLA-B or HLA-DR types,20 and an initial report suggesting involvement of chromosome 1p21.1–1q25.321 was not confirmed in two large, multigeneration pedigrees (96 individuals, 25 affected) 19. CARD15 polymorphisms were also excluded in a pilot study and a case series 22 23.…”
Section: Risk Factors: Smoking Obesity and Family Historymentioning
confidence: 91%
“…35 A later and larger study of HLA in Swedish patients compared with a population sample did not find any HLA-A, HLA-B, HLA-DR association. 36 One study describing an autosomal dominant pattern of inheritance has also been reported, but the penetrance appeared variable, indicating that other nongenetic factors are involved. 26,37 A later review of the data has renewed the suspicion of a dominant pattern of inheritance in this group of patients using a better clinical definition of the cases.…”
Section: Etiology and Pathogenic Factorsmentioning
confidence: 94%
“…Specific genetic studies have yielded conflicting results. No significant HLA association has been reported [34]. Patients with a family history usually have milder disease with an earlier onset; this raises the question of heterogeneity of HS.…”
Section: Genetic Factorsmentioning
confidence: 96%